2017
DOI: 10.1007/s00209-017-1870-7
|View full text |Cite
|
Sign up to set email alerts
|

The second stable homotopy group of the Eilenberg–Maclane space

Abstract: We prove that for a finitely generated group G, the second stable homotopy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Many authors have studied bounds on the order of π 3 (SK (G, 1)) (cf. [1,6,7,17]). We deduce a finiteness criterion for π 3 (S X) in terms of π 2 (X ) and the number of tensors T ⊗ (G), where π 1 (X ) ∼ = G and S X is the suspension of the space X (see Remark 2.4).…”
Section: Theorem a Let X Be A Union Of Open Subspaces A B Such That mentioning
confidence: 99%
“…Many authors have studied bounds on the order of π 3 (SK (G, 1)) (cf. [1,6,7,17]). We deduce a finiteness criterion for π 3 (S X) in terms of π 2 (X ) and the number of tensors T ⊗ (G), where π 1 (X ) ∼ = G and S X is the suspension of the space X (see Remark 2.4).…”
Section: Theorem a Let X Be A Union Of Open Subspaces A B Such That mentioning
confidence: 99%
“…Many authors had studied bounds to the order of π 3 (SK(G, 1)) (cf. [1,6,7,17]). Now, we can deduce a finiteness criterion for π 3 (SX) in terms of π 2 (X) and the number of tensors T ⊗ (G), where π 1 (X) ∼ = G and SX is the suspension of a space X (see Remark 2.4, below).…”
Section: An Application Of Theoremmentioning
confidence: 99%
“…To prove (1), it is enough to restrict ourselves to p groups using a standard argument given in Theorem 4, Chapter IX of [27]. A. Lubotzky and A. Mann showed that (1) holds for powerful p groups( [15]), M. R. Jones in [13] proved that (1) holds for groups of class 2, P. Moravec showed that (1) holds for groups of nilpotency class at most 3, odd order class 4, potent p groups, metabelian p groups of exponent p, p groups of class at most p − 2 ( [19], [20], [21]) and some other classes of groups. The general validity of (1) was disproved by A. J. Bayes, J. Kautsky and J. W. Wamsley in [3].…”
Section: Introductionmentioning
confidence: 99%
“…This problem has remained open even for finite p groups of class 5 having odd exponent. The purpose of this paper is to prove (1) for finite p groups of class 5 with odd exponent and to also prove the above mentioned results of [15], [19], [20] and [21] for odd primes and hence proving all these results using a common technique and bringing them under one umbrella. We briefly describe the organization of the paper by listing the main results according to their sections.…”
Section: Introductionmentioning
confidence: 99%